Divergent Synthesis of Quinoline Derivatives via [5+1] Annulation of 2‐Isocyanochalcones with Nitroalkanes. Issue 9 (6th April 2018) - Bao, Lan; Liu, Jinglin; Xu, Liang; Hu, Zhongyan; Xu, Xianxiu
Abstract: An unprecedented substrate‐dependent [5+1] annulation of 2‐isocyanochalcones with nitroalkanes was developed for the efficient synthesis of functionalized quinolines and 3‐nitrodihydroquinolines. This transformation delivers both the aromatic and dihydroquinolines by selectively elimination or retention of the nitro group. Moreover, 3‐nitroquinolines and tricyclic pyrrolo[2, 3‐ c ]quinolines were conveniently constructed from the resulting 3‐nitrodihydroquinolines through a single operation, respectively. Abstract :